Two mechanisms of conduction in polycrystalline SnO2 - Malagú, C. (2009)
Impedance spectroscopy was carried out on SnO2 thick films exposed to different atmospheres. Oxygen desorption and adsorption during heating and cooling processes, respectively, onto the grain surface affects the resistance and electrical capacitance of the sensors. Double parabolic Schottky-type potential barriers at grain boundaries were assumed to analyze the tunneling and thermionic contributions to conductivity. In addition, the influence of the temperature on the oxygen diffusion into the grains annihilating oxygen vacancies was studied. It was deduced that in-diffusion substantially affects the conductivity. © 2008 Elsevier B.V. All rights reserved.